2023
DOI: 10.1021/acsami.2c22038
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Vanadium Redox Reaction in Na3V2(PO4)3 Cathodes for Sodium-Ion Batteries by the Synergistic Effect of Additional Electrons from Heteroatoms

Abstract: Na 3 V 2 (PO 4 ) 3 (NVP) is one of the most potential cathode materials for sodium-ion batteries (SIBs), but its actual electrochemical performance is limited by the defects of large electron and ion transfer resistance. Multicomponent design is considered an effective method to optimize the conductivity of NVP electrodes. Therefore, Cr and Si are added in NVP to form a multielement component of Na 3 V 1.9 Cr 0.1 (PO 4 ) 2.9 (SiO 4 ) 0.1 (NVP-CS). It is confirmed that 3d electrons of Cr are beneficial for impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In general, the decreased I D /I G value after K-substitution indicates the higher degree of graphitization and improved electronic conductivity, possibly resulting from catalytic graphitization of K source introduced in the precursor. 19,52,54 For the K-NVP@C/MWCNT, the introduction with MWCNT induces the increased disordered species in the composite, leading to the higher of I D /I G value. 22,47,55 S2 (Supporting Information) exhibits the TGA curves of NVP@C, K-NVP@C, and K-NVP@C/MWCNT, and the weight loss of 3.7, 4.2, and 7.6%, respectively, corresponds to the carbon contents in the three samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the decreased I D /I G value after K-substitution indicates the higher degree of graphitization and improved electronic conductivity, possibly resulting from catalytic graphitization of K source introduced in the precursor. 19,52,54 For the K-NVP@C/MWCNT, the introduction with MWCNT induces the increased disordered species in the composite, leading to the higher of I D /I G value. 22,47,55 S2 (Supporting Information) exhibits the TGA curves of NVP@C, K-NVP@C, and K-NVP@C/MWCNT, and the weight loss of 3.7, 4.2, and 7.6%, respectively, corresponds to the carbon contents in the three samples.…”
Section: Resultsmentioning
confidence: 99%
“…For the Raman spectra, the D band at around 1360 cm –1 and the G band at 1590 cm –1 , corresponding to the disordered structure and ordered domain, can be clearly observed (Figure c). In general, the decreased I D / I G value after K-substitution indicates the higher degree of graphitization and improved electronic conductivity, possibly resulting from catalytic graphitization of K source introduced in the precursor. ,, For the K-NVP@C/MWCNT, the introduction with MWCNT induces the increased disordered species in the composite, leading to the higher of I D / I G value. ,, Figure S2 (Supporting Information) exhibits the TGA curves of NVP@C, K-NVP@C, and K-NVP@C/MWCNT, and the weight loss of 3.7, 4.2, and 7.6%, respectively, corresponds to the carbon contents in the three samples. In principle, the in situ generated carbon coating layer from the pyrolysis of citric acid and introduction of MWCNT can not only accelerate the migration of electrons but also contribute to maintaining the integrity of electrode, resulting in improved electrochemical performance .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for higher specific capacity and energy density of lithium-ion batteries (LIBs) has risen urgently due to its wide use in electric vehicles, electronic devices, energy storage power stations, and many other fields. Compared with commercial graphite anode material (372 mAh g –1 ), Si-based anode materials stand out for their high capacity (4200 mAh g –1 for Li 22 Si 5 and 3579 mAh g –1 for Li 15 Si 4 ) and low Li-uptake voltage (≈0.4V), and are considered promising candidates for the next-generation LIBs. However, the Si anode has some tough problems, which hinder its further development and commercial application. On the one hand, the severe volume expansion (∼400%) during the lithiation process leads to the pulverization of the active particles, causing loss of electrical contact and decrease in capacity. On the other hand, the semiconductivity of Si makes it unsatisfying for transmission of electrons and ions, resulting in poor rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al demonstrated, that doping low amounts of cost-efficient Fe 2 + ions activates the V 4 + /V 5 + redox, which leads to a large reversible capacity of 133 mAh g À 1 . [9] Multicomponent doping of Cr and Si [10] or the combined approach of carbon coating together with Nb 5 + substitution into the crystal structure [11] recently proved the enhancement of the electronic conductivity of NVP composites. Beside this crystal-chemical modification of the NASICON structures, a different viable approach is microstructure engineering.…”
Section: Introductionmentioning
confidence: 99%